The Swedish Experience of Fiscal Reform: Lessons for Portugal - Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2014)
This paper derives a set of policy lessons for Portugal from the new fiscal framework including a fiscal policy council that gradually emerged in Sweden after the deep economic crisis of the early 1990s. By now, Swedish public finances stand out among the strongest in Europe. Recent Swedish macroeconomic performance has been impressive. As Sweden and Portugal are small open economies in the periphery of Europe, Sweden may serve as a fiscal model for Portugal. Policy lessons are distilled from the Swedish experience for Portugal, stressing the importance of the economic policy culture for macroeconomic outcomes and for trust in government institutions and policies.
Keywords: E52; E62; E63; E65; F44; H62; O52; 330; Fiscal rules; fiscal policy council; fiscal policy; public debt; Sweden; Portugal.